2012
DOI: 10.1603/en11153
|View full text |Cite
|
Sign up to set email alerts
|

Host-Range Testing of Eucryptorrhynchus brandti (Coleoptera: Curculionidae), a Candidate for Biological Control of Tree-of-heaven, Ailanthus altissima

Abstract: Ailanthus altissima (Mill.) Swingle, tree-of-heaven, is an invasive species native to Asia. It first was introduced into the United States in the 1700 s and now is distributed throughout much of North America. Mechanical and chemical controls are current suppression tactics, however, implementation is costly. A weevil, Eucryptorrhynchus brandti (Harold), was identified in China and imported for quarantine testing in 2004 as a potential biological control agent. Host specificity tests on adult feeding, larval d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Tree of heaven is native to China and is an invasive plant in North America . It is an important part of the landscape, and because of it is highly tolerant of poor air quality and soils, it is found particularly in shelter belts, which are widely planted in provinces in northern China . There have been a number of reports of damage to and even death of A. altissima and A. altissima var.…”
Section: Introductionmentioning
confidence: 99%
“…Tree of heaven is native to China and is an invasive plant in North America . It is an important part of the landscape, and because of it is highly tolerant of poor air quality and soils, it is found particularly in shelter belts, which are widely planted in provinces in northern China . There have been a number of reports of damage to and even death of A. altissima and A. altissima var.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Herrick, McAvoy, Snyder, Salom, and Kok (2012) report that E. brandti is highly host specific and poses no or little risk to nontarget species. While this study showed that E. brandti may be a secondary pest in China, it is also considered a pest in its native range and is controlled to reduce damage and death to A. altissima.…”
Section: Discussionmentioning
confidence: 99%
“…When considering introduction of a biological control agent, information on its impact in its native range is important in assessing the benefits and risks of introduction (Legner & Bellows, 1999). Eucryptorrhynchus brandti is being considered as a candidate for biological control in the USA and was found to be highly host specific to A. altissima (Herrick, McAvoy, Snyder, Salom, & Kok, 2012). A successful rearing method was developed by Herrick, Salom, Kok, and McAvoy (2011).…”
mentioning
confidence: 99%
“…The weevil Eucryptorrhynchus brandti (Harold) (Coleoptera: Curculionidae), is a destructive wood‐boring insect pest of tree‐of‐heaven, Ailanthus altissima (Mill.) Swingle (Sapindales: Simaroubaceae) in China . Tree‐of‐heaven is native to China and extensively planted for soil and water conservation and shelter belts in northern China .…”
Section: Introductionmentioning
confidence: 99%